2018
DOI: 10.1111/gbb.12475
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte gene expression is reduced by and influences effects of chronic social stress in mice

Abstract: Oligodendrocyte gene expression is downregulated in stress-related neuropsychiatric disorders, including depression. In mice, chronic social stress (CSS) leads to depression-relevant changes in brain and emotional behavior, and the present study shows the involvement of oligodendrocytes in this model. In C57BL/6 (BL/6) mice, RNA-sequencing (RNA-Seq) was conducted with prefrontal cortex, amygdala and hippocampus from CSS and controls; a gene enrichment database for neurons, astrocytes and oligodendrocytes was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 75 publications
(206 reference statements)
6
62
2
1
Order By: Relevance
“…In agreement with these observations, animal studies on depression have also demonstrated that values of~30-40 genes were altered when mice were exposed to chronic unpredictable mild stress. Among them are OL-associated genes such as MBP, MOB and CNP [99][100][101]. For instance, the CNP gene encodes the enzyme 2′,3′-cyclic nucleotide 3′-phosphodiesterase (CNP), which is expressed in the development of OLs and increases with the onset of myelination and remains detectable throughout life [102].…”
Section: Myelin-regulated Genes and Myelination In Depressionmentioning
confidence: 99%
“…In agreement with these observations, animal studies on depression have also demonstrated that values of~30-40 genes were altered when mice were exposed to chronic unpredictable mild stress. Among them are OL-associated genes such as MBP, MOB and CNP [99][100][101]. For instance, the CNP gene encodes the enzyme 2′,3′-cyclic nucleotide 3′-phosphodiesterase (CNP), which is expressed in the development of OLs and increases with the onset of myelination and remains detectable throughout life [102].…”
Section: Myelin-regulated Genes and Myelination In Depressionmentioning
confidence: 99%
“…For motor learning, both mice subject to optogenetic stimuli and complex wheel activity display changes in myelin structure (Gibson et al, 2014;McKenzie et al, 2014;Xiao et al, 2016). In addition, mice housed in social isolation demonstrate changes in white matter (Liu et al, 2012) and mice subject to chronic social stress have decreased expression of oligodendrocyte genes and myelination (Lehmann et al, 2017;Cathomas et al, 2019). Thus, myelin plasticity may be crucial for behavioral responses to environmental changes and future studies should investigate the molecular involvement of TPPP in microtubule-based myelin structural in response to learning.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of myelin after adolescent perturbations are still limited, but evidence from adult examination suggests this is an important area of study. Alterations of myelin thickness and oligodendrocyte number have been displayed following adult models of chronic stress . In adult male Sprague‐Dawley rats, 4 weeks of chronic unpredictable stress increased depressive‐like behaviors, as evidenced by a decrease of sucrose consumption.…”
Section: Myelin Maturationmentioning
confidence: 99%
“…Alterations of myelin thickness and oligodendrocyte number have been displayed following adult models of chronic stress. 63,107 In adult male Sprague-Dawley rats, 4 weeks of chronic unpredictable stress increased depressive-like behaviors, as evidenced by a decrease of sucrose consumption. This behavioral change was accompanied by a decrease in the oligodendrocyte markers MBP and oligodendrocyte transcription factor 2 (Olig2).…”
Section: Synaptic Maturationmentioning
confidence: 99%